BRMS1 gene expression may be associated with clinico-pathological features of breast cancer. Issue 4 (21st August 2017) - Lin, Li-Zhong; Cai, Miao-Guo; Dai, Yue-Chu; Zheng, Zhi-Bao; Jiang, Fang-Fang; Shi, Li-Li; Pan, Yin; Song, Han-Bing
Abstract : Our aim is to investigate whether or not the breast cancer metastasis suppressor 1 ( BRMS1 ) gene expression is directly linked to clinico-pathological features of breast cancer. Following a stringent inclusion and exclusion criteria, case–control studies with associations between BRMS1 and breast cancer were selected from articles obtained by way of searches conducted through an electronic database. All statistical analyses were performed with Stata 12.0 (Stata Corp, College Station, TX, U.S.A.). Ultimately, 1, 263 patients with breast cancer were found in a meta-analysis retrieved from a total that included 12 studies. Results of our meta-analysis suggested that BRMS1 protein in breast cancer tissues was significantly lower in comparison with normal breast tissues (odds ratio, OR = 0.08, 95% confidence interval (CI) = 0.04–0.15). The BRMS1 protein in metastatic breast cancer tissue was decreased than from that was found in non-metastatic breast cancer tissue (OR = 0.20, 95%CI = 0.13–0.29), and BRMS1 protein in tumor-node-metastasis (TNM) stages 1 and 2 was found to be higher than TNM stages 3 and 4 (OR = 4.62, 95%CI = 2.77–7.70). BRMS1 protein in all three major types of breast cancer was lower than that of control tissues respectively. We also found strong correlations between BRMS1 mRNA levels and TNM stage and tumor size. The results our meta-analysis showed that reduction in BRMS1 expression level was linked directly to clinico-pathological features of breast cancer significantly; therefore, suggesting the loss of expression or reduced levels of BRMS1 is potentially a strong indicator of the metastatic capacity of breast cancer with poor prognosis.